Effect of Physical Exercise on Heart Rate Variability in Persons with Down Syndrome - Melo, Geiziane Leite Rodrigues (2019)
Melo GLR, Soares BR, Neves RP, Olher RR, Souza LHR, Ferreira CES, Assumpção CO, Rosa TS, Boato EM, Moraes MR. Effect of Physical Exercise on Heart Rate Variability in Persons with Down Syndrome. JEPonline 2019;22(1):63-74. The purpose of this study was to analyze the effect of physical exercise on the parameters of heart rate variability (HRV) in people with Down syndrome (DS). A systematic review was carried out until December 2018, which included the following databases: (a) PubMed; (b) SCOPUS; and (c) Web of Science. A combination of keywords relating to HRV and exercise was included during the research process. Initially, 570 articles were found, of which 7 were included in the sample. The 7 studies included in the present review tested 20 interventions and involved 245 participants. Interventions included aerobic training (n = 14), resistance training (n = 2), and concurrent training (n = 4). The results indicated that both aerobic and strength training and combined exercise can improve the parasympathetic modulation even with attenuated response of heart rate and blood pressure during and after physical exercise. Therefore, it is suggested that people with DS should practice some type of exercise to enhance their sympatho-vagal balance and to improve their health status.